Nutritional quality of rainbow trout (Oncorhynchus mykiss) caught from the Ataturk Dam Lake in Turkey - Celik, Mehmet; Goekce, Mahmut Ali; Basusta, Nuri; Kuecuekguelmez, Ayguel; Tasbozan, Oguz; Tabakoglu, S. Surhan (Wiley, 2008)
This study was carried out to determine the proximate, fatty acid, cholesterol, mineral and trace element compositions of the rainbow trout (Oncorhynchus mykiss), which is commonly consumed in Turkey. The moisture, protein, lipid and ash contents of the rainbow trout were 71.65, 19.60, 4.43 and 1.36%, respectively. Total lipids were mainly characterized by low cholesterol levels (35.04 mg/100 g). The composition of fatty acids showed that total monounsaturated fatty acids (35.56%) were the highest, followed by saturated fatty acids (27.65%) and polyunsaturated fatty acids (23.09%). The mineral and trace elements determined were Ca, Na, K, P, Mg, Mn, Zn, Fe, Pb, Hg, As, Cd, Cu, Ni and Co. Among the minerals analyzed, K was the highest followed by Mg, Na, P and Ca. The most abundant trace elements were Co, Cu, Zn followed by Fe, and all trace elements were present in amounts below the limits proposed by the World Health Organization and the Turkish Food Codes for human consumption in the meat of rainbow trout.
Keywords: Fatty-Acid-Composition; Fresh-Water; Proximate Composition; Cholesterol Content; Fish; Muscle; Wild; Tissues; Safety